2005
DOI: 10.1016/j.jcrs.2004.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Surgery Survey 2004

Abstract: To determine the refractive surgery (RS) preferences of ophthalmologists worldwide, questionnaires were sent to 8897 members of the American Society of Cataract and Refractive Surgery. A total of 1053 questionnaires were returned by the deadline. The practice distribution included 29.5% cataract surgeons, 48.8% comprehensive ophthalmologists, 11.6% RS specialists, 5.1% cornea and external disease specialists, 1.9% glaucoma specialists, 1.1% retina specialists, and <1.0% oculoplastics/pediatrics/researchers/ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
28

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 2 publications
0
42
1
28
Order By: Relevance
“…Overall 13.3% (57/429) of patients underwent PTK, 1.6% (7/429) PRK, 59.7% (256/429) LASIK, and 25.4% The popularity of LASIK is mirrored in the 2004 USRS; 7 however in contrast to this study (65.2 vs 8.7%) PRK is still more popular than LASEK in US (PRK (71%) vs LASEK (40.8%)) 7 even though there is a shift towards LASEK.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…Overall 13.3% (57/429) of patients underwent PTK, 1.6% (7/429) PRK, 59.7% (256/429) LASIK, and 25.4% The popularity of LASIK is mirrored in the 2004 USRS; 7 however in contrast to this study (65.2 vs 8.7%) PRK is still more popular than LASEK in US (PRK (71%) vs LASEK (40.8%)) 7 even though there is a shift towards LASEK.…”
contrasting
confidence: 70%
“…[4][5][6][7][8] Five per cent of the respondents had performed excimer therapy in the previous month and all were corneal specialists.…”
mentioning
confidence: 99%
“…However, in many Brazilian and international centers (2,6) , microkeratome blades are reused in bilateral surgery and in different patients, despite the absence of any studies comparing the results of this system and the possible risks. There is a lack of studies on this subject and, except that by Prandi et al who showed better functional results with thin flaps (<100 µm) in cases of myopia, the impact of the loss of flap quality observed under electron microscopy on the complication rate and final results is, to our knowledge, not known (11) .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Dryness is also a common complication after laser in situ keratomileusis (LASIK), a commonly performed surgical procedure to correct refractive error. 78 The trauma to the corneal surface from this procedure results in myopic or hyperopic correction, but also presents an increased risk for dry eye. 79,80 There is little evidence comparing LASIK outcomes for different ethnic groups, but one study observed an increased risk of chronic dry eye in Asians post-LASIK.…”
Section: Symptomatology: Dryness and Discomfort With Contact Lens Wearmentioning
confidence: 99%